Modifications of 7-hydroxy- 3-(benzothiazol-2-yl)coumarin - Shokol, T.V.; Suprun, A.V.; Hlibov, E.K.; Moskvina, V.S.; Khilya, V.P. (Reports of the National Academy of Sciences of Ukraine, 2021)
This paper is devoted to 7-hydroxy-3-(benzothiazol-2-yl)coumarin modifications using the dimethylaminomethyl and formyl groups introduced in 8 position, useful for further structural transformations. Derivatives of the dihydrooxazinocoumarin system were obtained by aminomethylation of 7-hydroxy-3-(benzothiazol-2-yl) coumarin under the classical Mannich reaction conditions using an excess of formalin. Starting from 8-dialkylaminomethyl-7-hydroxy-3-(benzothiazol-2-yl)coumarin the corresponding Mannich bases were synthesized by transamination with benzylamines, homoisoflavone derivatives were obtained as a result of the interaction with o-hydroxyarene enaminoketones and 3-(benzothiazol-2-yl)-7-hydroxy-8-formylcoumarin was obtained under the Duff reaction conditions. The latter in the reaction with 4-nitrophenacyl bromide formed the furo[2,3-h]coumarin system derivative. The recyclizations of 3-(benzothiazol-2-yl)-7-hydroxy- 8-(4-oxo-4H-3-chromenylmethyl)-2H-2-chromenone under the action of binucleophiles were studied.